Diabetes mellitus - factors that contribute to the occurrence, diagnosis and management of the disease - Čizmić Milica; Ristić Petar; Đuran Zoran; Karajović Jelena; Zoranović Uroš; Nenezić Nemanja (Vojnosanitetski Pregled)
nema